Community health workers at the dawn of a new era: 9. CHWs' relationships with the health system and communities - Karen LeBan; Maryse Kok; Henry B. Perry (BMC, 2021)
Abstract Background This is the ninth paper in our series, "Community Health Workers at the Dawn of a New Era". Community health workers (CHWs) are in an intermediary position between the health system and the community. While this position provides CHWs with a good platform to improve community health, a major challenge in large-scale CHW programmes is the need for CHWs to establish and maintain beneficial relationships with both sets of actors, who may have different expectations and needs. This paper focuses on the quality of CHW relationships with actors at the local level of the national health system and with communities. Methods The authors conducted a selective review of journal articles and the grey literature, including case study findings in the 2020 book Health for the People: National CHW Programs from Afghanistan to Zimbabwe. They also drew upon their experience working with CHW programmes. Results The space where CHWs form relationships with the health system and the community has various inherent strengths and tensions that can enable or constrain the quality of these relationships. Important elements are role clarity for all actors, working referral systems, and functioning supply chains. CHWs need good interpersonal communication skills, good community engagement skills, and the opportunity to participate in community-based organizations. Communities need to have a realistic understanding of the CHW programme, to be involved in a transparent process for selecting CHWs, and to have the opportunity to participate in the CHW programme. Support and interaction between CHWs and other health workers are essential, as is positive engagement with community members, groups, and leaders. Conclusion To be successful, large-scale CHW programmes need well-designed, effective support from the health system, productive interactions between CHWs and health system staff, and support and engagement of the community. This requires health sector leadership from national to local levels, support from local government, and partnerships with community organizations. Large-scale CHW programmes should be designed to enable local flexibility in adjusting to the local community context.